2015
DOI: 10.1371/journal.pone.0135988
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Estrogen Receptor 1 Mediates Acute Estrogen-Induced Cardioprotection via MEK/ERK/GSK-3β Pathway after Ischemia/Reperfusion

Abstract: Three types of estrogen receptors (ER) exist in the heart, Esr1, Esr2 and the G protein-coupled estrogen receptor 1, Gper1. However, their relative importance in mediating estrogen protective action is unknown. We found that, in the male mouse ventricle, Gper1 transcripts are three- and seventeen-fold more abundant than Esr1 and Esr2 mRNAs, respectively. Analysis of the three ER knockouts (Esr1-/-, Esr2-/- and Gper1-/-) showed that only the Gper1-/- hearts lost their ability to be protected by 40 nM estrogen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 40 publications
4
55
1
Order By: Relevance
“…For instance, Pugach et al reported that ERβ was not expressed in either neonatal or adult male or female mouse or rat ventricular myocytes. This observation is inconsistent with earlier reports . In addition, there are controversies surrounding the cellular localization of GPR30.…”
Section: Classification Localization and Distribution Of Ers In The Cvscontrasting
confidence: 87%
“…For instance, Pugach et al reported that ERβ was not expressed in either neonatal or adult male or female mouse or rat ventricular myocytes. This observation is inconsistent with earlier reports . In addition, there are controversies surrounding the cellular localization of GPR30.…”
Section: Classification Localization and Distribution Of Ers In The Cvscontrasting
confidence: 87%
“…It could stimulate the MEK1/2-ERK1/2 pathway, which in turn induces GSK3-β phosphorylation preventing opening of mPTP, or it could act straight to GSK3-β to prevent mPTP opening. These evidences uphold once again the role that the RAF/ MEK/ERK signaling pathway has in cardioprotection, this is supported by several articles in Literature (Grohé, Kahlert, Löbbert, & Vetter, 1998;Hausenloy & Yellon, 2009;Kabir et al, 2015;Node et al, 1997) Studies revealed how, in cardiomyocytes, the RAF/MEK/ERK pathway carries out in pressure-overloaded myocardium an important role for the development of hypertrophy and ribosomal biogenesis. It regulates hypertrophic gene induction, even though it could be not sufficient for cellular morphological changes necessary for cardiomyocyte hypertrophy.…”
Section: Pathophysiological Mechanisms Of Cardiovascular Toxicity Of mentioning
confidence: 61%
“…To identify the receptor required for estradiol's protective effects, Kabir and colleagues subjected hearts from male mutant mice lacking either GPER, ERα or ERβ to ischemia-reperfusion injury in the presence of estradiol or vehicle. Estradiol treatment protected wildtype and ERα and ERβ mutant mice from injury, but had no effect on GPER mutant mice (35), demonstrating that estradiol exerts its protective effects via GPER, independently of ERα or ERβ. The extent to which ER and GPER signaling pathways interact likely depends on cell type, developmental stage, sex and/or pathology.…”
Section: Discussionmentioning
confidence: 91%